Բոսֆորից մինչև Խաղաղ օվկիանոս․ Մտորումներ ՀՀ ԳԱԱ Արևելագիտության ինստիտուտի 35-ամյակի առթիվ - Հովհաննիսյան, Նիկոլայ («Զանգակ - 97»)
Establishment of the Institute of Oriental Studies, NAS Armenia, in 1971, was an ouistanding event in the scientific life of Armenia and turning point in the history of ihe Armenian Orientalistics. The main area of studies for the institute at that time was defined the Middle East and the attention of the Armenian Orientalists was focused on the study of the Arab countries, Turkey, Iran, Kurdish problems, Christian Easl and Ancient East. The article deals with different stages of development of Oricntalistics in Armenia, the main tasks, standing before the Institute in each stage, and us achievcments. Since the establishment of the Armenian Orienatalistic center it was published about 350 monographs and several thousands of scientific articles by the Armenian rescarchers, some of which in abroad in English, Arabic, Russian, Turkish, Persian, Germany, France, Italian, Japanese etc.
Keywords: Պատմություն